2021
DOI: 10.1055/s-0041-1740442
|View full text |Cite
|
Sign up to set email alerts
|

Administration and Toxicity Profile of the Capizzi Interim Maintenance—Retrospective Study from a Tertiary Care Cancer Centre

Abstract: Introduction The Capizzi-style methotrexate (MTX) is an integral part of acute lymphoblastic leukemia (ALL) treatment. The escalating dose of MTX originally used in the United Kingdom and Children’s Oncology Group protocols along with L-asparaginase has been modified in the Indian Childhood Collaborative Leukemia (ICiCLe) group protocol where L-asparaginase has been omitted. The data regarding the incidence of toxicities and ease of administration on the Capizzi-style interim maintenance is not robust. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Two retrospective reviews from India reported that 28.7 to 52% of children with leukemia and lymphoma treated with C-MTX experienced some toxicity, most often elevated transaminases, febrile neutropenia, and thrombocytopenia. 15,16 However, no nephrotoxicity or multiorgan failure was reported, and no obese children were reported. Both studies noted that undernourished children were at increased risk of toxicity, 15,16 which was thought to be due to liver dysfunction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two retrospective reviews from India reported that 28.7 to 52% of children with leukemia and lymphoma treated with C-MTX experienced some toxicity, most often elevated transaminases, febrile neutropenia, and thrombocytopenia. 15,16 However, no nephrotoxicity or multiorgan failure was reported, and no obese children were reported. Both studies noted that undernourished children were at increased risk of toxicity, 15,16 which was thought to be due to liver dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 However, no nephrotoxicity or multiorgan failure was reported, and no obese children were reported. Both studies noted that undernourished children were at increased risk of toxicity, 15,16 which was thought to be due to liver dysfunction. 15 They discussed that prehydration and posthydration may have a role in mitigating toxicity risk, 15 which is not standard of care in the United States.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation